Tolerance of latissimus dorsi in immediate breast reconstruction without implant to radiotherapy. Issue 1 (January 2018) - Berthet, G.; Faure, C.; Dammacco, M.A.; Vermesch, C.; Delay, E.; Ho Quoc, C.; Carrabin, N.
Summary: Introduction: Immediate breast reconstruction (IBR) improves the quality of life of patients who undergo mastectomy. The latissimus dorsi flap (LDF) method provides particularly good aesthetic results, but its tolerance to subsequent radiotherapy remains unclear. We thus sought to assess tolerance and esthetic results and satisfaction, as reported by patients who underwent IBR by LDF with or without subsequent radiotherapy. Materials and methods: We performed a retrospective case–control study in a population of women who were diagnosed with breast cancer between January 1999 and January 2014 and who had mastectomies with IBR by LDF without prostheses. We paired 29 patients who needed postoperative radiotherapy to 58 control patients who did not. These patients responded to a questionnaire to evaluate tolerance and their satisfaction with the aesthetic results of the reconstruction. Results: In total, 86.2% of all patients reported "very good" or "good" overall aesthetic satisfaction. Consistency was judged as "very good" or "good" by 82.7% of control patients and by 93.1% of case patients. No statistically significant differences were identified between the two groups with regard to reconstruction results. The number of surgical procedures needed did not differ significantly between the two groups. Conclusion: In our study, IBR by LDF appeared to have excellent tolerance to subsequent radiotherapy, the latter having no impact on patient aesthetic satisfaction. Our results suggest that the possibility of postoperative radiotherapy should not prevent physicians from proposing this method to women who are candidates for it.